Impacto das áreas de preservação permanente sobre a erosão hídrica na bacia hidrográfica do Rio da Prata, Castelo-ES - Coutinho, Luciano Melo (2010)
A watershed is the primary unit of water resource management, because their behavior affects the hydrological occurrence and magnitude of water erosion. Hydrologic simulation models, which allow to estimate the hydrology and water erosion, consisting of important management tool to minimize environmental degradation in these units. The Permanent Preservation Areas (PPA) are defined for protection of natural resources by density of vegetation. The aim of the present work was undertaken, in Silver Basin (Castelo ES) studies relief (guided by different sources of elevation data and interpolation procedures) and quantification of the annual erosion (under different scenarios of land use). This end, we worked in an environment of Geographic Information Systems, data relief (topographic maps and radar images) and land use (aerial photography), which allowed the manipulation of data and generation of factors of interest on the proposed procedures, and: a) evaluate the delimitation of the Silver Bowl from different digital elevation models; b) classify the forms of natural cover and use and land cover; c) delimit the areas considered as PPA; d) apply Universal Soil Loss Equation (USLE) the scenarios of land use and occupancy with respect to PPA. The delineation manual, generated by the topographical map of Castelo-ES and interpolation by interpolating isolines Topo to Raster , supported consisted hydrography, respectively, the method delimitation and interpolating the best performance the delimitation of basin, therefore, alternatives adopted for subsequent studies. The main physical characteristics of the River Plate basin are drainage area 132.28 Km², average elevation 593m and mean slope 39.77%. Pastures are the main form of land use in the basin, clean pasture (24.01%) and dirty pasture (6.62%), followed by permanent crops (27.26%). The portion corresponding to PPA equivalent to 55.48% of the basin (73.39 km²). The average annual erosion are 85.43 ton/ha/ year actual use of soil and 27.50 ton/ha/ year when adopting PPA, difference of 32.20%